2013
DOI: 10.1128/jcm.00481-13
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Kittens Is Associated with a Shift in Ileum Mucosa-Associated Enterococci from Enterococcus hirae to Biofilm-Forming Enterococcus faecalis and Adherent Escherichia coli

Abstract: e Approximately 15% of foster kittens die before 8 weeks of age, with most of these kittens demonstrating clinical signs or postmortem evidence of enteritis. While a specific cause of enteritis is not determined in most cases, these kittens are often empirically administered probiotics that contain enterococci. The enterococci are members of the commensal intestinal microbiota but also can function as opportunistic pathogens. Given the complicated role of enterococci in health and disease, it would be valuable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 52 publications
2
43
1
Order By: Relevance
“…The potential for disparity has been highlighted using E. coli isolated from people in which the growth of biofilm varied according to growth medium, bacterial source, and nutrient availability . Despite this, the assay remains a valid approximation used frequently in studies because of its affordability, feasibility, and lack of invasiveness. Assessing in vivo biofilm formation may require bladder biopsy, which would likely decrease potential subject enrollment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for disparity has been highlighted using E. coli isolated from people in which the growth of biofilm varied according to growth medium, bacterial source, and nutrient availability . Despite this, the assay remains a valid approximation used frequently in studies because of its affordability, feasibility, and lack of invasiveness. Assessing in vivo biofilm formation may require bladder biopsy, which would likely decrease potential subject enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…In the veterinary literature, biofilm studies, in particular those involving E. coli , are uncommonly reported, and are limited to case reports of nonurinary diseases such as wounds ( Staphylococcus [pseud]intermedius , Staphylococcus epidermidis , Streptococcus canis) , otitis externa ( Pseudomonas aeruginosa ), implant infections ( S. pseudintermedius ), and experimental endometritis in horses ( P. aeruginosa ) . Similarly, few studies in veterinary medicine describe the increased pathogenicity that biofilms confer, which includes increased mortality in kittens with gastrointestinal dysbiosis ( Enterococcus faecalis , E. coli ), and implied increased severity of bovine mastitis . We are unaware of any published study that compares the population or clinical characteristics of dogs with biofilm‐forming E. coli UTIs to nonbiofilm‐forming E. coli UTIs.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment was considered to be efficacious against individual isolates if a significant difference (P Ͻ 0.05) in disruption or killing of bacteria was observed. that in human medicine (25,49,50). The results presented in this research agree with other published studies performed in human and veterinary medicine, in which the majority of bacterial isolates associated with disease are capable of forming a biofilm in vitro (17, 25, 43-46, 48, 49).…”
Section: Discussionmentioning
confidence: 99%
“…5,17,20,38,55,88,89,115,117,119,126 These microbial changes are accompanied by underlying susceptibilities in the innate immune system of dogs and cats with chronic enteropathies, such as idiopathic IBD, further demonstrating the relationship between gut microbiota and host health. 55,62,63,78,86 It is been shown that the canine microbiota changes with diarrhea, with the most profound changes in dogs with acute hemorrhagic diarrhea (AHD), 117 and characterized by significant decreases in Blautia, Ruminococcaceae including Faecalibacterium, and Turicibacter spp., and significant increases in genus Sutterella and Clostridium perfringens compared to healthy dogs (Fig.…”
Section: The Microbiome In Gastrointestinal Diseasesmentioning
confidence: 99%